2015
DOI: 10.1002/jbmr.2557
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effect of Estrogen on Human Bone Marrow Fat

Abstract: Bone marrow fat, an unique component of the bone marrow cavity increases with aging and menopause and is inversely related to bone mass. Sex steroids may be involved in the regulation of bone marrow fat, because men have higher bone marrow fat than women and clinical observations have suggested that the variation in bone marrow fat fraction is greater in premenopausal compared to postmenopausal women and men. We hypothesized that the menstrual cycle and/or estrogen affects the bone marrow fat fraction. First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 32 publications
1
53
1
Order By: Relevance
“…In addition, there may be crosstalk between leptin, estrogen and the GH-IGF-1 axis, both of which are suppressed in CR in humans and animal models (Devlin et al 2010; Misra and Klibanski 2011; Mobbs, et al 2001). Postmenopausal estrogen deficiency in women is associated with MAT expansion, and estrogen replacement increases serum leptin and decreases marrow adiposity (Limonard, et al 2015; Syed, et al 2008). GH deficiency leads to expansion of MAT that is attenuated by GH replacement in dwarf ( dw/dw) rats (Gevers, et al 2002) and in hypophysectomized mice and rats (Menagh, et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there may be crosstalk between leptin, estrogen and the GH-IGF-1 axis, both of which are suppressed in CR in humans and animal models (Devlin et al 2010; Misra and Klibanski 2011; Mobbs, et al 2001). Postmenopausal estrogen deficiency in women is associated with MAT expansion, and estrogen replacement increases serum leptin and decreases marrow adiposity (Limonard, et al 2015; Syed, et al 2008). GH deficiency leads to expansion of MAT that is attenuated by GH replacement in dwarf ( dw/dw) rats (Gevers, et al 2002) and in hypophysectomized mice and rats (Menagh, et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the mineralized component, bone marrow characterization remains an important aspect of better understanding the pathophysiology of bone loss induced by both primary and secondary osteoporosis. In addition to the relationship between bone marrow fat fraction and BMD in primary osteoporosis, bone marrow fat changes have been also reported in secondary osteoporosis patients, like patients with chronic kidney disease, in prostate cancer patients treated with androgen deprivation therapy, and in women receiving estrogen …”
Section: Future Research Directionsmentioning
confidence: 99%
“…61 The changes in marrow adiposity are most evident in the axial skeleton and it has been reported that the increase in MAT can occur quickly after withdrawal of estrogen or decrease rapidly in response to exogenous estrogen. 62 Furthermore, the fatty acid composition of MAT in postmenopausal women also follows a similar profile demonstrating lower saturated fatty acids and increased monounsaturated fatty acids, particularly in participants with previous fracture. 63 This is particularly interesting given the opposite observation in T2DM.…”
Section: Clinical Scenarios Of Altered Mat and Their Bone Phenotypementioning
confidence: 82%